2011
DOI: 10.2460/ajvr.72.12.1576
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maropitant, a neurokinin 1 receptor antagonist, on anesthetic requirements during noxious visceral stimulation of the ovary in dogs

Abstract: Maropitant decreased the anesthetic requirements during visceral stimulation of the ovary and ovarian ligament in dogs. Results suggest the potential role for neurokinin 1 receptor antagonists to manage ovarian and visceral pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 34 publications
3
72
0
7
Order By: Relevance
“…Maropitant can provide analgesic effect by blocking the pharmacological action of substance P at the spinal cord and brain [1, 7, 30]. NSAIDs produce analgesic and anti-inflammatory effects by inhibiting the production of prostaglandins [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maropitant can provide analgesic effect by blocking the pharmacological action of substance P at the spinal cord and brain [1, 7, 30]. NSAIDs produce analgesic and anti-inflammatory effects by inhibiting the production of prostaglandins [35].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, maropitant is expected to provide analgesic effects by preventing the substance P from binding with the NK 1 receptors located in the dorsal horn. It is reported that maropitant decreased the anesthetic requirements in dogs [1, 7]. …”
mentioning
confidence: 99%
“…The true pain-modifying effect of maropitant in dogs remains uncertain despite canine studies revealing an anesthetic-sparing effect and a non-inferior effect to morphine in an ovariohysterectomy model. 85,86 Bisphosphonates Administered by iV infusion, this class of drug exerts antiosteoclast activity and can contribute to pain relief in dogs with bone cancer.…”
Section: Maropitantmentioning
confidence: 99%
“…Metoclopramide and maropitant are used as antiemetic (Simpson, 2007). For the latter drug, an analgesic action has been hypothesised due to its antagonism toward the NK1 receptors, implicated in the transmission of the painful stimuli (Boscan et al, 2011b).…”
Section: Gastric Erosions/ulcersmentioning
confidence: 99%
“…An aggressive fluid therapy and an antibiotic, antiemetic and antidiarrheal therapy is recommended, but no analgesic drugs are usually included in the protocol. However, between antiemetic drugs, maropitant can have some analgesic effect (Boscan et al, 2011b). Opioids are recommended only in case of intussusception, when a surgical approach is needed (Hedlund and Fossum, 2008).…”
Section: Acute Enteritismentioning
confidence: 99%